PENGEMBANGAN MEDIA PEMBELAJARAN NAHWU BERBASIS MACROMEDIA FLASH 8 UNTUK MENINGKATKAN HASIL BELAJAR SANTRI - M Wildan Awwiby; Afif Kholisun Nashoih; Aufia Aisa (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Nahwu is a science that studies the rules of the Arabic language. Nahwu is the main lesson in pesantren education. One of pesantrens is Al-Muhajirin 1 Jombang Islamic boarding school, the students are required to master the nahwu lessons. Based on the results of observations and interviews, the researcher concluded that students' understanding of the nahwu was low, for example in the i'rob chapter, some students were not able to memorize the divisions and signs of i'rob. This is because the learning media used is only a blackboard, so students feel bored during the learning process. The purpose of this study was to determine how the development of nahwu learning media based on macromedia flash 8 to improve the learning outcomes of students at Pondok Al-Muhajirin 1 class 1 and to find out the effectiveness of these learning media. This study uses the ADDIE model of research and development (R&D) method. The data collection technique was done by observing, interviewing and testing. The results of the validation of material experts reached 100% and media design experts 95%, indicating that this learning media reached a very decent level. Based on the results of the test (T) with the Paired Sample T Test, the value of T test 15,575 and T table 2,845 indicates the value of T Test> T Table. Then the hypothesis (H0) is rejected and (H1) is accepted, then the conclusion is that the use of nahwu learning media based on macromedia flash 8 is effective in improving student learning outcomes